2018
DOI: 10.1186/s13071-018-3173-1
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and current infections of canine vector-borne diseases in Nicaragua

Abstract: BackgroundVector-borne diseases constitute a major problem for veterinary and public health, especially in tropical regions like Central America. Domestic dogs may be infected with several vector-borne pathogens of zoonotic relevance, which may also severely compromise canine health.MethodsTo assess the prevalence of canine vector-borne diseases in Nicaragua, 329 dogs from seven cities, which were presented to the veterinarian for various reasons, were included in this study. Dogs were examined clinically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
4
14
1
Order By: Relevance
“…Additionally, A. phagocytophilum could be pathogenic for humans with potential zoonotic implications [58]. Due to their molecular similarity and cross-reactions, it is almost impossible to differentiate A. platys and A. phagocytophilum using serological analysis [59] while mixed infections are possible [60]. It was found that the overall prevalence of A. plat ys and/or A. phagocytophilum seropositivity was 6.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, A. phagocytophilum could be pathogenic for humans with potential zoonotic implications [58]. Due to their molecular similarity and cross-reactions, it is almost impossible to differentiate A. platys and A. phagocytophilum using serological analysis [59] while mixed infections are possible [60]. It was found that the overall prevalence of A. plat ys and/or A. phagocytophilum seropositivity was 6.2%.…”
Section: Discussionmentioning
confidence: 99%
“…While A. phagocytophilum has been previously reported from Rhipicephalus bursa ticks in Greece [29], as well as from Rhipicephalus spp. ticks from other areas, indicating that there is a potential also for these ticks to play a role in the transmission of A. phagocytophilum [30]. The primary tick vector for A. phagocytophilum, Ixodes ricinus, is only rarely found in Greece.…”
Section: Anaplasma Sppmentioning
confidence: 99%
“…Accordingly, previous surveys of canine vector-borne diseases in Central America have revealed high levels of exposure to Ehrlichia spp. (7, 10), followed by Anaplasma spp. (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…(7, 10), followed by Anaplasma spp. (10, 11). Both Anaplasma platys , the causative agent of canine cyclic thrombocytopenia, and Anaplasma phagocytophilum , causing zoonotic granulocytic anaplasmosis, are present in the region (10, 12, 13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation